Melatonin prevents formaldehyde-induced neurotoxicity in prefrontal cortex of rats: an immunohistochemical and biochemical study - Zararsiz, Ismail; Kus, Ilter; Ogeturk, Murat; Akpolat, Nusret; Kose, Evren; Meydan, Sedat; Sarsilmaz, Mustafa (Wiley, 2007)
This study was undertaken to investigate the protective effects of melatonin against formaldehyde-induced neurotoxicity in prefrontal cortex of rats. For this purpose, 21 male Wistar rats were divided into three groups. The rats in Group I were used as a control, while the rats in Group II were injected every other day with formaldehyde. The rats in Group III received melatonin daily while exposed to formaldehyde. At the end of 14-day experimental period, all rats were killed by decapitation. The brains of the rats were removed and the prefrontal cortex tissues were obtained from all brain specimens. Some of the prefrontal cortex tissue specimens were used for determination of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) levels. The remaining prefrontal cortex tissue specimens were used for immunohistochemical evaluation. The levels of SOD and GSH-Px were significantly decreased, and MDA levels, were significantly increased in rats treated with formaldehyde compared with those of the controls. In the immunohistochemical evaluation of this group, apoptotic cells were observed. However, increased SOD and GSH-Px enzyme activities, and decreased MDA levels, were detected in the rats administered melatonin while exposed to formaldehyde. Furthermore, apoptotic changes caused by formaldehyde were decreased in these rats. The results of our study suggest that melatonin treatment prevents formaldehyde-induced neuronal damage in prefrontal cortex. Copyright (C) 2006 John Wiley & Sons, Ltd.
Keywords: formaldehyde; melatonin; prefrontal cortex; rat; neurotoxicity